Özelleştirme ve Türkiye - Eniştekin, Mehmet Fatih (My University, 2004)
Bu çalışmamızda Türkiye gündemini 80'li yıllardan beri meşgul eden özelleştirme kavramı hakkında verilmiştir. Çalışmamız 3 ana bölümden oluşmaktadır. Özelleştirme Kavramına Genel Bakış ismini taşıyan birinci bölümümüzde özelleştirme kavramının tanımı ve özelleştirmenin gerekçeleri incelenmiştir. Özelleştirme Yönetmeleri ve Dünya'da Özelleştirme Yaklaşımı başlıklı ikinci bölümümüzde sırasıyla sekiz ana özelleştirme yöntemi ayrıntılarıyla anlatılmıştır. Daha sonra özelleştirmenin dünyadaki gelişimi Dünya'da Özelleştirme Yaklaşımı başlığı altında incelenmiştir. Yasal Kurumsal ve Uygulama Açısından Türkiye'de Özelleştirme başlıklı üçüncü bölümümüzde ise özelleştirmenin bugüne kadarki kanunlardaki yeri incelenmiştir. Ayrıca, özelleştirme ilkelerine değinilmiş ve özelleştirme çalışmalarının kurumsal yapısı hakkında bilgi verilerek, Türkiye'deki özelleştirme çalışmaları özetlenmiştir.

There has been given general information about the privatization, a term that has been up-to-date since the 80's in Turkey, in our study. Our study consists of three major chapters. In the first chapter named A General Overview of the Privatization the definition of the privatization and its justification has been analyzed. In the second chapter titled Privatization Methods and the Approaches to the Privatization in the World eight major privatization methods has been explained elaborately. Afterwards, the development of the privatization in the world has been analyzed in the chapter titled The Approaches to the Privatization in the World. In the third chapter titled The Privatization in Turkey from the Legal, Institutional and Implementation Perspectives the place of the privatization in the laws up to now has been analyzed. Besides, the privatization principles have been touched upon and by giving information about the institutional structure of the privatization work; the privatization works in Turkey has been summarized.
Keywords: Özelleştirme_Türkiye